Dual blockade of PI3K and MEK in combination with radiation in head and neck cancer. (June 2018) - Blas, Kevin; Wilson, Thomas G.; Tonlaar, Nathan; Galoforo, Sandra; Hana, Alaa; Marples, Brian; Wilson, George D.
Abstract: Background and purpose: In this study we have combined fractionated radiation treatment (RT) with two molecular targeted agents active against key deregulated signaling pathways in head and neck cancer. Materials and methods: We used two molecularly characterized, low passage HNSCC cell lines of differing biological characteristics to study the effects of binimetinib and buparlisib in combination with radiation in vitro and in vivo . Results: Buparlisib was active against both cell lines in vitro whereas binimetinib was more toxic to UT-SCC-14. Neither agent modified radiation sensitivity in vitro . Buparlisib significantly inhibited growth of UT-SSC-15 alone or in combination with RT but was ineffective in UT-SCC-14. Binimetinib did cause a significant delay with RT in UT-SCC-14 and it significantly reduced growth of the UT-SCC-15 tumors both alone and with RT. The tri-modality treatment was not as effective as RT with a single effective agent. Conclusions: No significant benefit was gained by the combined use of the two agents with RT even though each was efficacious when used alone.